Locus of Control and Psychological Well-Being in Single Women of the Toraja Tribe who Have a Career - Maharani, Dhea Lhaksmita; Huwae, Arthur (Psikostudia : Jurnal Psikologi, 2024)
Locus of control is one of the important factors in improving psychological well-being. This is also in line with what is experienced by single women of the Toraja tribe who have a career, for them being single and having a career is not an easy thing because of the many demands and pressures they feel. To be able to improve psychological well-being, it is necessary to have a locus of control for single women of the Toraja tribe who have a career so that they are expected to be able to overcome the problems they are facing. This study aims to determine the relationship between locus of control and psychological well-being in single women of the Toraja tribe who have a career. The method used is correlational quantitative. There were 110 single women of the Toraja tribe who have a career as participants in this study using a purposive sampling technique. This study uses two scales the IPC LOC (Internality, Powerful Others dan Chance Locus of Control) and the Scales of Psychological Well-Being. The result of hypothesis testing with Karl Pearson is .533 with sig = .000 (p<.01), which means this is accepted. These results proves that locus of control is one of the factors related to the achievement of psychological well-being in single women of the Toraja tribe who have a career. This means a relationship exists between an increase or decrease in locus of control and an increase or decrease in psychological well-being. The results obtained show that locus of control is one of the factors associated with the achievement of psychological well-being in single women of the Toraja tribe who have a career. This research provides a new understanding of the positive meaning of the community in seeing the role of women as part of the sacredness of Toraja local culture who are also responsible for the role or involvement to realize every cultural demand that is an obligation for each community. In addition, despite the highest degree of men's position in Toraja local culture who are responsible for every realization of daily family needs and customs, but still place women as a balance of life that helps the family take responsibility for a career and meet every demand of custom patently applies.Locus of control menjadi salah satu faktor yang penting dalam meningkatkan kesejahteraan psikologis. Hal ini juga sejalan dengan yang dialami oleh perempuan lajang suku Toraja yang berkarier, bagi mereka melajang dan berkarier bukan merupakan suatu hal yang mudah karena banyaknya tuntutan serta tekanan yang dirasakan. Untuk dapat meningkatkan kesejahteraan psikologis, maka diperlukan adanya locus of control dari dalam diri perempuan lajang suku Toraja yang berkarier agar diharapkan mampu mengatasi masalah yang sedang dihadapi. Penelitian ini bertujuan untuk mengetahui hubungan antara locus of control dengan kesejahteraan psikologis pada perempuan lajang suku Toraja yang berkarier. Metode yang digunakan adalah kuantitatif korelasional. Terdapat 110 perempuan lajang suku Toraja yang berkarier dijadikan partisipan dalam penelitian ini dengan menggunakan teknik purposive sampling. Penelitian ini menggunakan dua skala yang terdiri atas IPC LOC (Internality, Powerful Others dan Chance Locus of Control) dan Scales of Psychological Well-Being. Hasil yang diperoleh menunjukkan bahwa locus of control menjadi salah satu faktor yang berhubungan dengan pencapaian kesejahteraan psikologis pada perempuan lajang suku Toraja yang berkarier. Penelitian ini memberikan pemahaman baru mengenai makna positif masyarakat dalam melihat peran perempuan sebagai bagian dari kesakralan budaya lokal Toraja yang turut bertanggung jawab atas peran atau keterlibatannya untuk mewujudkan setiap tuntutan budaya yang menjadi kewajiban bagi setiap masyarakat. Selain itu, meskipun posisi laki-laki lebih tinggi dalam budaya lokal Toraja yang bertanggung jawab dalam setiap realisasi kebutuhan keluarga dan adat istiadat sehari-hari, namun tetap menempatkan perempuan sebagai penyeimbang kehidupan yang membantu keluarga dalam bertanggung jawab baik itu secara berkarier maupun memenuhi setiap tuntutan adat istiadat yang berlaku secara turun temurun.